1993
DOI: 10.1152/ajpendo.1993.265.6.e839
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of oxidative stress in skeletal muscle atrophied by immobilization

Abstract: To clarify the mechanism of oxidative stress in skeletal muscle atrophied by immobilization, we measured the activities of antioxidant enzymes and xanthine oxidase (XOD) and carried out the cytochemical study of hydrogen peroxide in a typical slow red muscle, the soleus. Male Wistar rats (15 wk old), of which ankle joints of one hindlimb were immobilized in the fully extended position, were killed after 4, 8, or 12 days. The activities of Mn-containing superoxide dismutase (Mn-SOD), Cu-Zn-containing superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(194 citation statements)
references
References 12 publications
11
175
2
5
Order By: Relevance
“…Some studies have reported that unloading causes oxidative stress such as overexpression of reactive oxygen species, leading to capillary regression in the atrophied muscle 15,16) . Although elevation of reactive oxygen species was not observed in the present study, the overexpression of reactive oxygen species has been shown in similarly atrophied muscles in other studies 4,5) , and in the present study, atrophied plantaris muscle may have been exposed to oxidative stress. Unsaturated fatty acids, a major component of mitochondrial membrane, are oxidized by reactive oxygen species 17) , and astaxanthin has been shown to inhibit lipid peroxidation 18) .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Some studies have reported that unloading causes oxidative stress such as overexpression of reactive oxygen species, leading to capillary regression in the atrophied muscle 15,16) . Although elevation of reactive oxygen species was not observed in the present study, the overexpression of reactive oxygen species has been shown in similarly atrophied muscles in other studies 4,5) , and in the present study, atrophied plantaris muscle may have been exposed to oxidative stress. Unsaturated fatty acids, a major component of mitochondrial membrane, are oxidized by reactive oxygen species 17) , and astaxanthin has been shown to inhibit lipid peroxidation 18) .…”
Section: Discussioncontrasting
confidence: 62%
“…Muscle atrophy involves capillary regression, which is also more marked in oxidative muscle than in glycolic muscle 3) . It has been reported that inactivity results in overexpression of reactive oxygen species in atrophied muscle 4,5) , leading to capillary regression 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria contributes to muscle ROS production during immobilization [52, [54][55][56], but other studies highlight that XO plays also an important role [57,58]. To the best of our knowledge no studies reported that NOX, NOS or ER plays a role in the production of ROS induced by immobilization.…”
Section: Skeletal Muscle Oxidative Stress In Immobilization and Physimentioning
confidence: 99%
“…Thus, ATP is synthesized as necessary by myocyte mitochondria. Meanwhile, oxidative stress has been reported to increase in muscle tissue when activity is restricted, such as when immobilized in a cast or splint 40) . In sarcopenia, this is thought to increase the generation of active oxygen in mitochondria, which increases the damage to muscle tissue 41) .…”
Section: Changes In Muscle Type During Atrophymentioning
confidence: 99%